Pulmonary rehabilitation: focusing on rehabilitative exercise - Casaburi, Richard (Henry Stewart Talks, 2012)
Pulmonary Rehabilitation, Historical perspective on pulmonary rehabilitation, Current evidence-based guidelines for pulmonary rehabilitation, Activity promotion as a novel goal for pulmonary rehabilitation
Archived at 2022/07/31